Effect of Strong Welding Flow on the Violence of Low Carbon Steel Results of SMAW Welding with Electrodes 7018 - Jasman, Jasman; Irzal, Irzal; Pebrian, Pebrian (Universitas Negeri Padang, 2018)
Welding can be interpreted by the process of joining two metals to the molten metal point. Metal low carbon steel which is easily processed by welding techniques. Strong setting of the welding current will affect the weld. If the current used is too low it will cause the difficulty of igniting the electric arc. Conversely, if the welding current is too high, the electrode will melt too fast. The welding current strength 130A corresponds to the diameter of the 3.2 mm electrode. The purpose of the research was to determine whether or not the influence of welding current on the low carbon steel hardness of SMAW welding results with E7018 electrode. This type of research was carried out by the type of experimental research, the research process was carried out by hardness testing, and the data obtained through the results of hardness testing was followed by observation and analysis of specimens of low carbon steel ST 37 welded by SMAW with different current strength using E-7018 electrode. Low carbon steel specimens from SMAW welding with 130 A welding current using E-7018 electrode have a higher hardness value compared to low carbon steel specimens produced by SMAW with welding current strengths of 100A and 160A using E-7018 electrodes.